2023
DOI: 10.3389/fimmu.2023.1103617
|View full text |Cite
|
Sign up to set email alerts
|

Roles of macrophages on ulcerative colitis and colitis-associated colorectal cancer

Abstract: Colitis-associated colorectal cancer is the most serious complication of ulcerative colitis. Long-term chronic inflammation increases the incidence of CAC in UC patients. Compared with sporadic colorectal cancer, CAC means multiple lesions, worse pathological type and worse prognosis. Macrophage is a kind of innate immune cell, which play an important role both in inflammatory response and tumor immunity. Macrophages are polarized into two phenotypes under different conditions: M1 and M2. In UC, enhanced macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 130 publications
0
12
0
Order By: Relevance
“…Our findings revealed that the high-risk group had a predominant enrichment of macrophages and pDCs, while the low-risk group had a predominant enrichment of Th2 cells. It has been reported that high infiltration of macrophages exacerbates the progression of ulcerative colitis to colon cancer and is considered a poor prognostic marker 52 , 53 . Similarly, extensive infiltration of pDCs predicts a poor prognosis in breast and ovarian cancer 54 , 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings revealed that the high-risk group had a predominant enrichment of macrophages and pDCs, while the low-risk group had a predominant enrichment of Th2 cells. It has been reported that high infiltration of macrophages exacerbates the progression of ulcerative colitis to colon cancer and is considered a poor prognostic marker 52 , 53 . Similarly, extensive infiltration of pDCs predicts a poor prognosis in breast and ovarian cancer 54 , 55 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we did not address dendritic cells such as macrophages. Tumorassociated macrophages (TAMs) are a diverse population of immune cells that play a complex role in CRC and probably in CAC prognosis [44]. Macrophages can polarize into M1 and M2 types, with distinct roles.…”
Section: Discussionmentioning
confidence: 99%
“…The type and location of TAMs can have different prognostic significance: M2 TAMs have been associated with poor CRC prognosis, and high M1 macrophage and CD68+TAM infiltration is correlated with a better prognostic situation in CRC patients [45]. The transition from UC to CAC involves two key processes, namely inflammation and tumorigenesis, both of which involve macrophages [44]. For example, in the UC inflammatory phase, excessive macrophage infiltration could worsen the inflammation by inducing proinflammatory cytokine production and promoting CAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophage polarization refers to the dynamic process by which macrophages transition into activated states under specific conditions ( Murray, 2017 ). In normal physiological circumstances, intestinal macrophages phagocytose microorganisms and initiate a controlled immune response as antigen-presenting cells ( Zhang et al, 2023 ). However, persistent and excessive inflammatory stimuli can lead to macrophage overactivation, which may damage the intestinal mucosa.…”
Section: Introductionmentioning
confidence: 99%